2023
DOI: 10.1111/1750-3841.16566
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of ultrasonic pretreatment on vacuum far‐infrared drying characteristics and quality of Angelica sinensis based on entropy weight‐coefficient of variation method

Abstract: This study investigated the effects of ultrasonic pretreatment time, ultrasonic power, and ultrasonic frequency on the drying characteristics and physicochemical quality of Angelica sinensis, and the physicochemical quality content was selected as the evaluation index, the entropy weight-coefficient of variation method was used to calculate the coupling weight and comprehensive score, and the weighted Technique for Order Preference by Similarity to Ideal Solution method was used to verify the evaluation model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…US pretreatment: peach slices were packed in polyethylene bags and placed to an ultrasound cleaner (KM-615B, Kemeng Ultrasonic Instruments Co., Ltd. Zhejiang, China), then 300 mL of distilled water was added. The US power 240 W, US frequency 40 kHz, US 20 min and water temperature 25℃ were selected as experimental conditions for US pretreatment, based on the preliminary research of US treatment on foods [6] , [40] . In addition, because the water temperature will rise during the US pretreatment process, this experiment uses a cooling water circulation device to control the temperature range of ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…US pretreatment: peach slices were packed in polyethylene bags and placed to an ultrasound cleaner (KM-615B, Kemeng Ultrasonic Instruments Co., Ltd. Zhejiang, China), then 300 mL of distilled water was added. The US power 240 W, US frequency 40 kHz, US 20 min and water temperature 25℃ were selected as experimental conditions for US pretreatment, based on the preliminary research of US treatment on foods [6] , [40] . In addition, because the water temperature will rise during the US pretreatment process, this experiment uses a cooling water circulation device to control the temperature range of ± 1 °C.…”
Section: Methodsmentioning
confidence: 99%
“…However, the high water content of fresh peaches after ripening leads to peak respiration and peak ethylene release, resulting in lower sensory quality and shorter postharvest life [5] . Drying is an effective method to prolong the shelf-life of fruits and vegetables by reducing moisture content and inhibiting quality deterioration caused by microbial growth [6] , [7] . At present, new drying technologies to improve drying rate and enhance product quality have attracted great attention from experts and researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Also, as pretreatment time increased, the Deff values increased. Zang et al, (2023) reported that increases in the ultrasonic pretreatment time of Angelica sinensis herbs caused an increase in the Deff values. During the UE pretreatment, cavitation was produced by ultrasonic waves, and the quince tissue was exposed to compression and expansion.…”
Section: Kinetics Of Dryingmentioning
confidence: 99%
“…Also, the cavitation phenomenon takes place during ultrasonic pretreatment due to the formation and collapse of air bubbles. The explosion of microbubbles produces strong shock wave energy, high pressure, shear force, and liquid jets that can help separation of water, which is strongly bound to the cell and can destroy the cell membrane (Pandiselvam et al, 2023;Zang et al, 2023). All of these phenomena lead to improvement in the mass transfer and movement of water from the interior to the surface of food and consequently improve the drying characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…IR rays penetrate the sample and turn into sensible heat, resulting in more uniform heating in IR drying (Huang et al., 2021) and may reduce the moisture gradient during heating and drying (Delfiya et al., 2022). The IR method was used individually or combined with different drying methods to dry kiwi fruit (Li et al., 2023b), turmeric slices (Jeevarathinam et al., 2022), chrysanthemum (Xu et al., 2022), rose petals (Li et al., 2024), Angelica sinensis (Zang et al., 2023), apple (El‐Mesery et al., 2024a), and pineapple (Tiliwa et al., 2022).…”
Section: Introductionmentioning
confidence: 99%